Civil Public Organizations for Providing a Public Order and their Role in Forming of Civil Society - YASTREBOVA, Anna I.; SALOMATKIN, Aleksandr S.; DZHAVAKHYAN, Roman M.; REDKOUS, Vladimir M.; FILONOV, Vladimir I. (Journal of Advanced Research in Law and Economics; Vol 7 No 2 (2016): JARLE, Volume VII, Issue 2(16), Spring 2016, 2016)
Relevance of the studied problem is caused by the needs of more complete involvement of the public associations created by citizens for providing a public order, to solve problems of formation of civil society for creation of the constitutional state in the Russian Federation. The purpose of article is to analyze the legal basis of participation of public associations in protection of a public order and to define the directions of improvement of its legal control. The leading approach of researching of this problem is the dialectic interrelation of development of state and legal institutes and institutes of civil society in order to achieve the highest possible personal, social and state security, according to existing conditions, from internal and external threats under which the realization of constitutional rights and freedoms of the Russian Federation citizens, good quality and level of their life, sovereignty, independence, the state and territorial integrity, sustainable social and economic development of the Russian Federation are provided. The article discloses the role of public organizations in providing public order, reasoning the necessity of improvement of their legal status, including citizens taking part in them. The article also analyze the Constitution of the Russian Federation, federal laws and normative legal acts, normative legal acts of the subjects of the Russian Federation (including Moscow, St. Petersburg, Altai Region) which regulate activity of public organizations within the constitutional state and also foreign experience of such associations in the USA, Great Britain, in countries of Western Europe. Summarizing this experience and it’s adaptation to theory and practice of our country is mostly appropriate. Materials of article can be used in educational process, and also in determining the directions of improvement of a legal basis of public organizations activities in providing a public order.